2006
DOI: 10.1038/sj.bjc.6602991
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of stathmin in oral squamous-cell carcinoma: correlation with tumour progression and poor prognosis

Abstract: Stathmin is an intracellular phosphoprotein that is overexpressed in a number of human malignancies. Our previous study using proteomic profiling showed that significant upregulation of stathmin occurs in oral squamous-cell carcinoma (OSCC)-derived cell lines. In the current study, to determine the potential involvement of stathmin in OSCC, we evaluated the state of stathmin protein and mRNA expression in OSCC-derived cell lines and human primary OSCCs. A significant increase in stathmin expression was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(81 citation statements)
references
References 27 publications
6
74
1
Order By: Relevance
“…To evaluate the anti-stathmin1 antibody in our lab, we performed immunohistochemistry using oral squamous cancer tissue. Stathmin1 was expressed in invading oral cancer cells ( Figure 1A), which was consistent with the previous report (Kouzu et al, 2006). In normal gastric mucosa, it was difficult to detect stathmin1 expression; however, we clearly observed cytoplasmic expression of stathmin1 in gastric cancer tissue and in metastatic gastric cancer cells (Figure 1).…”
Section: Immunohistochemical Analysis Of Stathmin1 þ Cells In Gastricsupporting
confidence: 91%
“…To evaluate the anti-stathmin1 antibody in our lab, we performed immunohistochemistry using oral squamous cancer tissue. Stathmin1 was expressed in invading oral cancer cells ( Figure 1A), which was consistent with the previous report (Kouzu et al, 2006). In normal gastric mucosa, it was difficult to detect stathmin1 expression; however, we clearly observed cytoplasmic expression of stathmin1 in gastric cancer tissue and in metastatic gastric cancer cells (Figure 1).…”
Section: Immunohistochemical Analysis Of Stathmin1 þ Cells In Gastricsupporting
confidence: 91%
“…19,20 In this study, overexpression of STMN1 was found to closely link to tumor differentiation, tumor size, N stage, and TNM stage. This result suggests that STMN1 could have a major role in tumor progression and dissemination.…”
Section: Discussionmentioning
confidence: 54%
“…As for these regulators in cancer cells, the catastrophe factors of MTs such as oncoprotein (Op)18/ stathmin were reported to be overexpressed in a number of human malignancies, and to be associated with cancer progression and prognosis (Roos et al, 1993;Bieche et al, 1998a, b;Brattsand, 2000;Chen et al, 2003;Moore and Wordeman, 2004;Kouzu et al, 2006). (C) Cell cycle analysis of MCAK transfectants and mock-transfected cells after 24 h of serum starvation followed by 18 h serum feeding with 10% FBS.…”
Section: Discussionmentioning
confidence: 99%